Berankis and Vargalys – Postcolonial Antiheroes? A Comparative Analysis of “Handless” and Vilnius Poker by Ričardas Gavelis - Piesinas, Markas Aurelijus (Colloquia, 2025)
This paper applies postcolonial theory to works by Lithuanian writer Ričardas Gavelis. It presents a comparative analysis of his short story “Handless,” published as part of the collection Nubaustieji (The Punished, 1987), and his novel Vilnius Poker (1989). A speech given by Lithuanian poet Sigitas Geda at a 1988 Sąjūdis rally, considered a potent expression of the postcolonial condition, serves as a conceptual reference point for the analysis. Gavelis’s novel and short story are viewed as examples of postcolonial literature, and the postcolonial concepts of liminality and mimicry are applied to these works. The antihero is understood as an inversion used for criticizing the Soviet regime. This paper posits that the antiheroic nature of Gavelis’s protagonists originates in their postcolonial condition.